2019
DOI: 10.3390/molecules24183215
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Gives New Insights into the Glucose Tolerance and Inhibition Mechanisms on β-Glucosidases

Abstract: β-Glucosidases are enzymes with high importance for many industrial processes, catalyzing the last and limiting step of the conversion of lignocellulosic material into fermentable sugars for biofuel production. However, β-glucosidases are inhibited by high concentrations of the product (glucose), which limits the biofuel production on an industrial scale. For this reason, the structural mechanisms of tolerance to product inhibition have been the target of several studies. In this study, we performed in silico … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 52 publications
4
28
0
2
Order By: Relevance
“…They act cleaving cellobiose in two molecules of glucose, which will be used in fermentation for producing bioethanol [3]. The design of thermostable and more efficient β-glucosidases enzymes has excellent value for the industry [4]; (ii) tobacco etch virus protease (PDB ID: 1LVB): proteases (peptidases) hydrolyze the peptide bond producing single amino acids or smaller polypeptides molecules. They are essential for several biological functions in all forms of life.…”
Section: Case Study 1: Evaluating Proteus Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…They act cleaving cellobiose in two molecules of glucose, which will be used in fermentation for producing bioethanol [3]. The design of thermostable and more efficient β-glucosidases enzymes has excellent value for the industry [4]; (ii) tobacco etch virus protease (PDB ID: 1LVB): proteases (peptidases) hydrolyze the peptide bond producing single amino acids or smaller polypeptides molecules. They are essential for several biological functions in all forms of life.…”
Section: Case Study 1: Evaluating Proteus Hypothesismentioning
confidence: 99%
“…The design of new proteins, known as protein engineering, has many applications for industry. Novel and likely enhanced proteins can benefit the development of new drugs, vaccines, treatment therapies, and improve the enzymes used in digestive processes for new food and biofuel production [1][2][3][4]. Industrial biotechnological applications require enzymes with higher thermal and conformational stability [5].…”
Section: Introductionmentioning
confidence: 99%
“…3.2.1.21) are enzymes that act in the last step of the saccharification process, cleaving cellobiose into two molecules of glucose 28,29 . Hence, they are considered very important for the second-generation biofuel industrial applications [30][31][32] . Besides, the literature has reported that most β-glucosidases are inhibited in high glucose concentrations 33,34 .…”
Section: Sars -Cov R1-r2mentioning
confidence: 99%
“…Overall, minimal topological modifications represent a promising strategy for suggesting mutations, especially in the beta-glucosidase loop regions that surround the active site. The topology and dynamics of these loops can allow or restrict movements involved in glucose entrance and exit (i.e., glucose tolerance) 30,32,36,43 or also can affect the thermostability [41][42][43] . These are both examples of industrially desirable characteristics for these and other proteins.…”
Section: Implications For Protein Engineeringmentioning
confidence: 99%
“…From these 15 proposed mutations, a previous study has provided experimental evidence of enhancing β-glucosidase activity even in high glucose concentrations for three of them: H228C, H228T, and H228V [9]. The residues mutated V302F, N301Q/V302F, F172I, V227M, G246S, T299S, and H228T were also the target of other computational studies that used classic and accelerated molecular dynamics simulation to highlight their role in glucose releasing [45,46]. Despite all these efforts, the rational design of more efficient βglucosidases is still a challenge.…”
Section: Introductionmentioning
confidence: 99%